BROCHE DE CINTURÓN VISIGODO PROCEDENTE DE PUEBLA DE D. FADRIQUE - Fernández Palmeiro, Jesús; Serrano Várez, Daniel (Antigüedad y Cristianismo, 1995)
Notification is made of a Visigothic belt bucke found out of context in Puebla de D. Fadrique to the northeast of Granada. It can be dated, using typological sirnilarities, to the sixth and seventh centuries a.c. The localization of its exact place of origin more difficult is because it was found in the sand bed of a ravla. Nevertheless the Visigothic presence in Granada is not unknown, as has been shown by the nearby sites of Baza and Tútugi.